THE CHALLENGES OF THE TECHNOLOGY 4.0 AND INFORMATION TECHNOLOGY WITHIN TOTAL WAR STRATEGY STRUCTURE - Arief, Ruslan; Risman, Helda; Sutanto, Rudy (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2021)
The development of information technology has a significant impact on various important aspects of life. Apart from positive impacts, there are also negative impacts that are important to know and anticipate to prevent major damage and losses. On a broad scale, namely at the national level, the development of information technology can also affect the development of national defense as it is known that the nature of Indonesia's defense is total defense, which is prepared to face the total war. Based on the explanation above, the purpose of this study is to examine the impact of the development of information technology on the implementation of Indonesia's total war strategy. The approach used is qualitative phenomenology with research data in the form of secondary data collected using literature studies. The data is then analyzed using qualitative analysis techniques. The results of the study indicate that the development of information technology has both positive and negative impacts. These impacts encourage the need for changes and adjustments to the total war strategy implemented by Indonesia. This is important to do so that Indonesia can have a stronger defense in preparation for a total war that may occur in the future.